THE PROBLEMS OF USING THE GOOGLE CLASSROOM APPLICATION IN THE ONLINE LEARNING PROCESS - Sri Hidayati Nur Ramadhan (MultiTech Publisher, 2023)
The purpose of this research is to find out The Problems of Using Google Classroom at SMA Muhammadiyah Maumere and find solutions to problems in using Google classroom at SMA Muhammadiyah Maumere. The type of research used in this research is qualitative and the data collection techniques used are observation and interviews. There were 18 informants in this research, namely 1 principal, 3 teachers, and 15 students at SMA Muhammadiyah Maumere. The results of this study are Problems in Using the Google Classroom Application at SMA Muhammadiyah Maumere experienced by teachers or students. The first obstacle faced by teachers is that not all students have cellphones or laptops. The second obstacle is network problems and running out of internet quota. While the obstacles experienced by students, the first obstacle is the internet network problem. The second obstacle is running out of internet quota, the third obstacle is lack of understanding of the material, The fourth obstacle is feeling full. Solutions made to overcome the problem of using Google Classroom students are advised to be able to use school Wi-Fi or the school can work with communication service providers. Students who not understand the material can ask the teacher via WhatsApp or discuss with friends, and can look for additional subject-related material on the internet or read it back in textbooks. Teachers must be creative and innovative.